F(-2).....this is basically saying that when x = -2, what is y
so f(-2) = 2
because f(x) is the same as y...but when u have f(-2)....this is saying x = -2 and they are wanting to know what y is....and when x = -2, y = 2....so f(-2) = 2
Answer:
122
Step-by-step explanation:
![x^6+y^2](https://tex.z-dn.net/?f=x%5E6%2By%5E2)
Plug in 1 for x and 11 for y
![=1^6+11^2](https://tex.z-dn.net/?f=%3D1%5E6%2B11%5E2)
1 to the power of any number will always equal 1
![=1+11^2\\=1+121\\=122](https://tex.z-dn.net/?f=%3D1%2B11%5E2%5C%5C%3D1%2B121%5C%5C%3D122)
I hope this helps!
Answer:
here is the answer
Step-by-step explanation:
Hello
the equation is y = ax+b
a the slop a = 4
y = 4x+b
the line <span>passes through (3, -10) : -10 = 6(3)+b
b = -28
</span>the equation is y = 6x-28
She had $100 and she gave $3 to her sister so $10-$3=$7 and her parent quadrupled her remaining dollars which was $7 so $7x4=$28 the answer is $28